2011
DOI: 10.1007/s13361-011-0147-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic NH and OH Vibrations for Oxazolone and Diketopiperazine Structures: b2 from Protonated Triglycine

Abstract: We present infrared multiple photon dissociation (IRMPD) spectra in the hydrogen stretching region of the simplest b fragment, b 2 from protonated triglycine, contrasted to that of protonated cyclo(Gly-Gly). Both spectra confirm the presence of intense, diagnostic vibrations linked to the site of proton attachment. Protonated cyclo(Gly-Gly) serves as a reference spectrum for the diketopiperazine structure, showing a diagnostic O-H + stretch of the protonated carbonyl group at 3585 cm -1 . Conversely, b 2 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…Although diketopiperazines are assumed to be the thermodynamically more stable isomers, oxazolones were found to prevail in many investigations [11,15,31,32,36,38,41,42,67]. The presence of histidine can apparently lower the high barrier to formation [66] of the two cis-amide bonds in diketopiperazines [39].…”
Section: Conformer-selective Vibrational Ir Spectramentioning
confidence: 99%
See 3 more Smart Citations
“…Although diketopiperazines are assumed to be the thermodynamically more stable isomers, oxazolones were found to prevail in many investigations [11,15,31,32,36,38,41,42,67]. The presence of histidine can apparently lower the high barrier to formation [66] of the two cis-amide bonds in diketopiperazines [39].…”
Section: Conformer-selective Vibrational Ir Spectramentioning
confidence: 99%
“…Room temperature IRMPD spectra in the XH stretching region were recently used to diagnose the protonation site in b 2 oxazolones [41,42], and structures with protonation at the oxazolone ring nitrogen have been reported as the major species observed in these investigations for the YI and GG b 2 ions, respectively. In contrast, under our conditions, we can largely exclude these in favor of species protonated on the N-terminal nitrogen atom for the YG b 2 ion.…”
Section: Conformer-selective Vibrational Ir Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the oxazolone structure can be confirmed via the presence of a lactone-type C=O stretch band, which appears in the high-frequency region (1770-1950 cm -1 ) of the midinfrared spectrum [24,25]. Studies by several groups have shown that smaller b fragments, such as b 2 , typically form oxazolone structures [18,21,[26][27][28]. An exception to this rule is the b 2 sequence motif His-Ala, which mainly adopts a diketopiperazine structure [19].…”
Section: Introductionmentioning
confidence: 99%